(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Shobha De’s writings explore the struggles and challenges faced by modern Indian women within the bond of marriage. The novels delve into the psychological and emotional aspects of marital relationships, exposing the enigma between traditional values and the desire for freedom and self-assertion. In Shobha De’s works, marriage is presented as a societal expectation where women are expected to make sacrifices and remain confined within the traditional roles. The protagonists, particularly the female characters, undergo internal conflicts as they grapple with the pressures of adhering to patriarchal norms while seeking personal fulfilment and liberation. These women desire equal rights and freedom within their marriages, but they are hindered by conservative societal expectations. The novels also highlight the impact of societal changes, liberalization, and gender issues on marital dynamics. The characters face dilemmas and emotional turmoil in their relationships as they navigate between their desire for autonomy and the societal pressures to conform. Extra-marital affairs and emotional struggles become common themes, reflecting the deep emotional void and psychological distress that some characters experience within their marriages. Shobha De’s portrayal of marriage emphasizes the importance of communication, understanding, and mutual respect in a successful union. The novels also shed light on the broader issues of gender equality and the need for societal transformation to empower women and create more equitable relationships. Shobha De’s critical study of marriage in her novels serves as a mirror to the complexities and challenges faced by modern Indian women in their pursuit of love, freedom, and self-discovery within the context of marriage and society.